Dimensional Analysis: A Second Generation Version of Grounded Theory Approaches - Mahmood Hashemi Afousi; Sajad Moemeni; Javad Shahlaee (Archives in Sport Management and Leadership)
In the realm of sports science research, familiarity with qualitative research methods and their specific strategies, such as Grounded Theory (GT), is crucial for conducting research and developing valid scientific theories. There are various versions of GT that can be classified into two categories: first generation (Classic, and Systematic) and second generation (Constructive, Situational Analysis, and Dimensional Analysis).  The attention of sports science researchers has grown significantly over qualitative research, especially using GT. However, it is evident that a predominant portion of existing research has employed first-generation GT versions. Further exploration of different versions of GT can play a significant role in selecting an appropriate version and presenting a more enriched theoretical framework. Consequently, this study introduces Dimensional Analysis (DA) as a second generation version of GT. This paper begins with a brief overview of the background, philosophical foundations, and emergence of DA, followed by a discussion and examination of the process of implementing DA.